Three- and Four-Nucleon Bound States in Three Dimensions, Without PW Decomposition - Hadizadeh, M. R. [UNESP]; Tomio, Lauro [UNESP] (American Institute of Physics (AIP), 2012)
A brief review of a three-dimensional (3D) numerical method to solve few-nucleon bound and scattering states, without the standard partial-wave (PW) decomposition, is presented. The approach is applied to three-and four-nucleon bound states, by considering the solutions of the corresponding Faddeev-Yakubovsky (FY) integral equations in momentum space. Realistic spin-isospin dependent 3D and PW formalism are presented for the alpha particle and the triton binding energies, with numerical results given in both schemes for comparison.
Keywords: 3N Bound State; 4N Bound State; Alpha Particle; Triton; Binding Energy; Faddeev-Yakubovsky Scheme; Three-Dimensonal Approach; 3N Force